A Comparative Histological Study of Effects of Cigarette and Shisha Smoke on Lungs of Mice - Shazia Imran, Huma Beenish, Kaukab Anjum, Hina Zaid (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The most popular way to take in tobacco is as cigarettes, which are now frequently accessible as vaporizers. When inhaled for an extended period of time, the smoke’s respiratory tract irritants cause fibrosis, inflammation, and precancerous diseases. Nicotine is the main alkaloid found in both commercial and home-made tobacco products, making up 0.6-3.0% of the dry weight of the tobacco plant. Aim: To compare the histological effects of cigarettes and shisha on the lungs of experimental animals. Study design: Randomized control trial. Methodology: A randomised control trial was used. In partnership with the National Institute of Health (NIH), Islamabad, the Department of Anatomy at the Islamic International Medical College in Rawalpindi developed and carried out this six-month study. 40 mature male BALB/c mice were allocated into three groups at random. Mice from the Control group C were housed in a fresh air- and smoke-exposed environment. Third Group CS was exposed to cigarette smoke, while Experimental Group SS was subjected to shisha smoke. Two exposures per day, five days per week, were administered. After a total of eight months of exposure, the subjects were dissected, the lung tissue was evaluated under a microscope, and the outcomes were compared across experimental groups. The quantity of carbon-loaded alveolar macrophages per unit was measured in the lung tissues. SPSS 20.0 was utilized to analyze the data. For quantitative histology data, mean and standard deviation were provided, while frequencies and percentages were provided for qualitative factors. The Pearson Chi Square test was used to determine the p value when comparing two groups and one way analysis of variance (ANOVA) was used to evaluate the mean differences between the control and experimental groups. Statistical significance was defined as a p-value of 0.05. Results: In comparison to group CS, group SS showed significantly more fibrosis, peribronchiolar inflammation, and bronchiolar constriction. Additionally, there were more carbon-loaded alveolar macrophages in group SS than in group CS, and this difference was statistically significant. Practical implication: As sheesha and vaping are now popular trends, this study will aid researchers in determining the risk linked with sheesha smoking. Conclusions: Shisha use is not a risk-free substitute for cigarette use. Compared to cigarette smoke, it has a larger concentration of toxicants that alter tissue at a far higher rate. Keywords: Shisha Smoke, Cigarette Smoke, Lungs Tissue, Mice and Histology.